Critical remarks on strategies aiming to reduce drug related harm: substance misuse and HIV/AIDS in a world in turmoil - Francisco Inácio Bastos; Carlos Linhares Veloso Filho (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
ABSTRACTIn the last decades, the initiatives implemented under the conceptual umbrella of Harm Reduction have gained momentum, with a vigor and scope (both from a geographic and social perspective) never seen before. A more balanced reevaluation could and should rather say such initiatives have resumed, to a large extent, ideas and actions launched much earlier, in the first decades of the 20th century. Notwithstanding, the dissemination of HIV/AIDS in recent years conferred an exceptional visibility and legitimacy to proposals formerly viewed as subsidiary or openly neglected. Nowadays, initiatives inspired by the Harm Reduction philosophy have faced an "identity crisis", not secondary (according to our perspective) to challenges faced by its concepts and operations, but rather as consequence of a world in a turmoil. Such fast-changing dynamics have reconfigured both drug scenes and the patterns and prospects of HIV/AIDS worldwide. This article briefly summarizes some of such recent, ongoing, changes, which have been deeply affecting both concepts and practices to the point of asking for a deep reformulation of most of the initiatives implemented so far.